ANALYSIS OF THE DECISION OF CASE NO. 1874 CONCERNING THE LEGALIZATION OF SIRI MARRIAGE - Tessa Pritama Eda (Media Inovasi Pendidikan dan Publikasi, 2023)
The legal requirements for marriage and the religious norms of the couple's chosen faith go hand in hand. There is no guarantee of legal certainty for either the couple or the offspring of such marriages, and society may make unfavorable presumptions about the couple and their children if they are involved in a series of marriages. The methodology uses normative legal research methods. Normative legal research or library research uses qualitative analysis, namely by explaining existing data with words or statements not with numbers. In the decision of Case No. 1874 K/Pdt/2013, the case examining judge who clearly contradicts the provisions contrary to the provisions of applicable legislation including citizenship laws concerning human rights, and the second principle of Pancasila and the 1945 Constitution that the siri marriage between the applicant and the respondent KASASII has been applied for Istibat Nikah at the Sleman Religious Court with Case Number 32/Pdt.G/2012/PA.Smn, and in the case decision it is stated that the siri marriage is valid according to Islamic law and legislation.